Model to improve cardiometabolic risk factors in Palestine refugees with diabetes mellitus attending UNRWA health centers. Issue 1 (18th August 2019) - Abu Kishk, Nada; Shahin, Yousef; Mitri, Joanna; Turki, Yassir; Zeidan, Wafaa; Seita, Akihiro
Abstract : Introduction The United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) is the main primary healthcare provider and provides assistance and protection to around 5 million Palestine refugees in Jordan, Lebanon, Syria, West Bank and Gaza. Diabetes mellitus (DM) is a common problem among Palestine refugees, with a prevalence of 11.0%. In 2014, UNRWA embarked on a diabetes campaign to assist both patients with DM and staff in improving diabetes care management, by building the capacity of UNRWA's health staff and improving the knowledge and lifestyle behaviors among Palestine refugees with DM. Method Using a quasiexperimental study, we randomly selected 50 patients with diabetes from the 32 largest UNRWA health centers (HC); a total of 1600 participants were enrolled. Each HC conducted weekly group sessions for 6 months, including education, healthy cooking, and physical exercise. Body measurements, 2-hour postprandial glucose test, blood pressure and session attendance were collected on a weekly basis. Demographical data, pre/postquestionnaires and cholesterol levels were collected before and after the campaign. Paired t-test in SPSS V.21 was used. Results Out of 1600 patients, 1598 (1186 (74.0%) females and 412 (26.0%) males) completed the campaign; 576 (36.0%) patients had diabetes type 2 (DMII), 960 (60.0%) had DMII and hypertension and 62 (4.0%) had diabetes type 1 (DMI). After the campaign, the average weight loss was 2.6 kg (95% CI 2.4 to 2.7). In addition, 22% lost ≥5%, 25% lost 3%–5%, and 30% lost 1%–3% of their weight. Significant improvements were seen in blood glucose, cholesterol and waist circumference (WC) (p≤0.001 for all). The session attendance rate was 70.6% in total. Conclusions This campaign focused on raising healthy lifestyle awareness and practices among Palestine refugees with DM. It was associated with reduction cardiometabolic risk factors. Similar campaigns need to be sustained and expanded. Local community and non-governmental organization partnerships observed during the campaign should be strengthened and sustained.